A Study on the Student Perception Survey to Improve the Quality of Field Practice - Noh, younghee (International Journal of Knowledge Content Development & Technology, 2024)
The purpose of this study was to propose ways to improve the library field practice of Department of Library and Information Science to improve the field environment and educational content, enhance students’ field practice, increase efficiency, and increase students’ satisfaction. To this end, a survey and interview survey were conducted on students who were going to do field training, and the results are as follows First, students were well aware of what preparations should be made at school before going to field training. Second, students showed high awareness of their rights guarantees and requests for action in the event of problems at field training institutions. Third, students showed a high demand that field training should guarantee the minimum hourly wage. What is an issue in this regard is that policies that can satisfy both the burden of universities for continuous student guidance and evaluation, the burden of training institutions to conduct education while paying practical expenses, and the rights of students to be protected. This study was aimed at students, but it seems that realistic field practice policies should be presented from various angles as research on government ministries or university authorities is added.